Contesting Water Rights Local, State, and Global Struggles - Subramaniam, Mangala (Springer International Publishing, 2018)
As globalization processes and related neoliberal agendas promote privatization through state action, people's struggles for rights to water have intensified. In this context, this book examines the role of the ambivalent state in local struggles for water, which are deeply intertwined with global forums that support and/or challenge the privatization of water resources. These local-global struggles have redefined the relationships between the state, corporations, and other social actors that impact the local politics of inequality and marginalization.